DIGITAL ENTREPRENEURSHIP EMPOWERMENT OF VOCATIONAL STUDENTS VIA DROPSHIPPING AND PRINT ON DEMAND IN THE DIGITAL AGE - Putri Irmala Sari; Supri Yanto; Suripto (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This community development initiative aimed to empower 50 students at SMK Negeri 7 Bandar Lampung through digital entrepreneurship training, specifically leveraging dropshipping and print on demand (POD) business models to enhance their economic adaptability in the digital era. The project employed a structured methodology comprising workshops, hands on technical training, and continuous mentoring sessions focused on platform utilization, product sourcing, design customization, digital marketing, and order fulfillment. Pre and post intervention assessments revealed significant improvements in participants digital literacy, entrepreneurial skills, and business operational competencies. Results demonstrated that 86% of students successfully established functional online stores, with 72% generating initial revenue within three month post-training. Additionally, participant surveys indicated a 95% increase in self efficacy regarding digital venture management and a strong intention to pursue entrepreneurship post-graduation. The initiative underscores the efficacy of targeted skill building in fostering youth economic resilience and reducing barriers to digital market entry.